Cancer Metastasis: The Role of the Extracellular Matrix and the Heparan Sulfate Proteoglycan Perlecan - Elgundi, Zehra; Papanicolaou, Michael; Major, Gretel; Cox, Thomas R.; Melrose, James; Whitelock, John M.; Farrugia, Brooke L. (Frontiers in Oncology, 2020)
Cancer metastasis is the dissemination of tumor cells to new sites, resulting in the formation of secondary tumors. This process is complex and is spatially and temporally regulated by intrinsic and extrinsic factors. One important extrinsic factor is the extracellular matrix, the non-cellular component of tissues. Heparan sulfate proteoglycans are constituents of the extracellular matrix, and through their heparan sulfate chains and protein core, and modulate multiple events that occur during the metastatic cascade. This review will provide an overview of the role of the extracellular matrix in the events that occur during cancer metastasis, primarily focusing on perlecan. Perlecan, a basement membrane heparan sulfate proteoglycan is a key component of the vascular extracellular matrix and is commonly associated with events that occur during the metastatic cascade. Its contradictory role in these events will be discussed and we will highlight the recent advances in cancer therapies that target heparan sulfate proteoglycans and their modifying enzymes.